The impact of Fartlak exercises to develop speed Endurance With basketball - Abdulrazak, Zahid Sbhee; Ahmed, Rana Shahab; Kareem, Odai Abdulhussein; Ahmed, Omar Saad (International Journal of Psychosocial Rehabilitation, 2020)
The aim of the study lies in knowing the effect of Codified Fartlek training on developing speed endurance. Whereas the significance illustrated that the speed endurance ability is a compound ability between speed and endurance. In these two the player exerts a physical effort with tension and for a fairly long time hence resisting all signs of exhaustion.In order to develop this ability, the Fartlek training By Holmer Style approach was used because its performance system is similar to performance. This approach is represented by running with changing speeds and for changing distances, then having a rest interval between walk and sprinting. This has been proper to the recent changes in basketball law.The hypothesis of the study is represented by finding out the differences in developing the speed endurance by Fartlek training (Holmer Style And Shaker Codified) in both the pre and post- tests and in favor of the post-test.The sample comprises Diyala ClubYoung basketballers aging (14-16 years). The sample amounted to (16) players who were divided into two groups, experimental and control. The study was carried out on the outdoor court of Al Khark Sports Club and the indoor court of the College of Physical Education/ University of Baghdad from19.6.2019 to 24.8.2019 .The speed endurance test was designed by experts and included 300m run. The researcher used the experimental method on the two equivalent groups as it suited the nature of the study. He also used the proper statistical means to analyze the results.Throughout the presentation and the analysis of the study results, the researcher has found significant differences in favor of the experimental group in the speed endurance test.The most important conclusions revealed that developing the speed endurance by means of the Fartlek method has a great effect in improving the player's ability and their acquiring of a good physical ability to resist exhaustion and to continue performing in high efficiency.The most significant recommendations fall in choosing the proper training methods and the physical characteristics suitable for the type of the game. Besides, this can be applied to other games such as football and handball.